(Des)caminhos de um devir-professora - Oliveira, Lidiane Martins de (2018)
In this dissertation I try to weave lines between the formation of teachers, the courses and meetings of my formation, gathered in a cartography. Putting across other glances through narratives and encounters with objects-devices that were part of my becoming a teacher. I enter Cartography as a methodological position, which is not articulated as a method, but as a means of displacement and diving in the field of education. From the meetings with the objects-devices - lab coat, letters, notebooks, postcards, book and chalk, marks of a course teacher, researcher, cartographer, outline and daydream telling and (des) believing from the invisibilities of events. I bring the idea of a (dis) path permeated by multiplicities, escaping and tearing the mark of a teacher with fixed identity and calcified by time. The meetings made possible in this research have the potential to stimulate other trajectories along the path of becoming teachers, to problematize the space and time of education and the teacher, to awaken learning through cracks, cracks and desires processes.